Effects of Garlic (Allium sativum) on Blood Glucose Level in Type 2 Diabetes Mellitus Patients Treated with Metformin (Journal of Enam Medical College, 2017)
Background: Diabetes mellitus is a heterogeneous group of metabolic disorders with microvascular and macrovascular complications which are the major causes of morbidity and mortality in diabetic patients. Anti-diabetic drugs are available in modern medicine, but prolonged use of these drugs may produce some side effects. Garlic due to some of its active components can improve glycemic status.Objective: To observe the effect of garlic (Allium sativum) in patients with type 2 diabetes mellitus with obesity.Materials and Methods: This prospective interventional study was carried out in the Department of Pharmacology & Therapeutics, Sir Salimullah Medical College (SSMC), Dhaka from July 2014 to June 2015. Total 60 type 2 diabetes mellitus with obesity subjects of both sexes in the age range 40 to 60 years were included in this study. They were selected on the basis of inclusion and exclusion criteria from Outpatient Department of Bangladesh Institute of Rehabilitation of Diabetes, Endocrine and Metabolic Disorder (BIRDEM) Hospital, Dhaka. The subjects were divided into two groups by simple random sampling. One was Group A and another was Group B. The subjects (30) of Group A were supplemented only metformin at a dose of 1000 mg per day. The subjects (30) of Group B were supplemented metformin at a dose of 1000 mg and garlic in capsule form at a dose of 500 mg per day. They were studied two times, on day-1 (1st day of metformin treatment, Group A1), on 12 weeks (after 12 weeks of metformin treatment, Group A2). Subjects of Group B were also studied two times on day-1 (before supplementation of garlic, Group B1) and on 12 weeks (after 12 weeks supplementation of garlic and metformin, Group B2). Fasting blood glucose level and postprandial blood glucose level of all subjects were measured by glucose oxidiase method. Blood HbA1c level of all participants was measured by immunoassay method. The statistical analysis was done by using paired and unpaired samplet test.Results: In this study, the mean FBG and PPBG levels decreased nonsignificantly (p>0.05) after 12 weeks treatment of metformin in comparison to 1st day of metformin treatment. Again, the mean FBG and PPBG levels decreased significantly after 12 weeks supplementation of metformin and garlic compared to before supplementation of garlic (p